Morinda Citrifolia (Noni) attenuated transcriptional and degenerative markers of cardiac toxicity in bisphenol A treated male wistar rats - Adewumi Oluwafemi Oyabambi; Blessing Boluwatife Aindero; Boluwatife Eunice Fashetan; Kofoworola Tinuola Oni (Journal of Functional Foods, 2023)
Bisphenol A (BPA) is an endocrine disruptor that causes metabolic disruption. It is widely used in the manufacturing industry as an internal protective lining for food and beverage cans. Morinda citrifolia (Noni) is a known ethno-medicinal plant of Pantropical origin. The aim of this study was to investigate the effect of Noni aqueous extract (NAE) on transcriptional and degenerative markers of cardiac toxicity in Bisphenol A treated male Wistar rats. Twenty-four male Wistar rats were randomly assigned into four groups as: Control (Ctr: normal chow + vehicle: Olive oil), BPA (7 g/kg, orally), (NAE:500 mg/kg; orally), and NAE: (500 mg/kg + BPA;7g/kg orally). After six weeks of administration, animals were anesthetized with 0.8 mg Phenobarbitone intraperitoneally and blood was collected by cardiac puncture. Plasma and cardiac homogenate were sampled and data were analyzed using a one-way ANOVA followed by Bonferroni’s Post hoc test. Results are expressed as mean ± standard error of mean (SEM) and p < 0.05 were accepted as significant. Bisphenol A reduced significantly plasma and cardiac histone deacetylate (HDAC), Nitric oxide (NO) and adenosine and increased triglycerides (TG), lipoprotein (a) or Lp(a), tumor necrotic factor alpha (TNF-α), uric acid (UA), and (malondialdehyde) MDA when compared with control and noni-treated group. NAE increased HDAC and NO significantly compared to the control while reducing significantly TNF-α, catalase, MDA, TG, and Lp(a). In conclusion, NAE reduced Bisphenol A worsening cardiovascular risks through a significant positive epigenetic HDAC expression and increased neovascularization activities.